Optical studies of the phase behavior of monodomain samples of dipalmitoyl phosphatidylcholine containing calcium chloride. - D'Ambrosio, C (1979)
Optical birefringence of the phases exhibited by monodomain samples of dipalmitoyl phosphatidylcholine containing 0.1 M-6 mM calcium chloride is measured over a range of temperature and water content. Little change was observed in the birefringence for this calcium chloride content range, and a phase diagram is constructed from these data and compared with that of monodomain samples of dipalmitoyl phosphatidylcholine and water. Effects of the presence of calcium chloride are most pronounced at low temperature and water content but the interaction with phosphatidylcholine cannot account for the effects observed with calcium on intermembrane interactions.